OPTIMALISASI FUNGSI RUANG TERBUKA HIJAU SEBAGAI RUANG PUBLIK DI TAMAN AYODIA KOTA JAKARTA SELATAN - Eko Sugiyanto; Cinly A. V Sitohang (Populis : Jurnal Sosial dan Humaniora, 2017)
This study aims to find out the optimization of open green space as a public space in Taman Ayodia Kota Jakarta Selatan. In this context, researchers utilize the concept of optimization, open green space, and construction administration. By using qualitative methods, researchers are then free to the perception of informants consisting of Kepala Sudin Pertamanan dan Pemakaman Kota Jakarta Selatan as well as the visitors of Taman Ayodia. The results show that the function of open green space in the location of the research turned out to be not optimal because there are several factors that affected it, that the parks still needs additions and improvements, in addition to various less activity. So open green space becomes the container of the social interaction of citizens that can create creativity and motor activity of visitors, required periodic and ongoing socialization.Keywords: optimization of the function of the Green open space, and public spaces.